2012
DOI: 10.1089/gtmb.2011.0152
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Arg399Gln and Arg194Trp Polymorphisms of the XRCC1 (X-Ray Cross-Complementing Group 1) Gene and Its Correlation to Sister Chromatid Exchange Frequency in Patients with Chronic Lymphocytic Leukemia

Abstract: Polymorphisms of the x-ray repair cross-complementing group 1 (XRCC1) gene have been reported to be associated with various forms of cancer. We evaluated the possible effects of the Arg194Trp and the Arg399Gln polymorphisms on the risk for chronic lymphocytic leukemia (CLL) in 73 patients and 50 controls. We also analyzed their relation to frequency of sister chromatid exchange (SCE). With respect to codon 194, the allelic frequency of the Arg194Trp polymorphism did not significantly differ between the 2 group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…We therefore excluded this study from Arg194Trp analysis. After removing these ineligible studies, a total 19 studies with 3387 cases and 6168 controls for Arg399Gln (G>A) polymorphism [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], 12 studies with 2043 cases and 4550 controls for Arg194Trp (C>T) [17], [18], [20], [21], [22], [23], [24], [25], [26], [28], [29], [32], and 6 studies with 1445 cases and 1905 controls for Arg280His (G>A) [15], [22], [23], [26], [28], [30] were included for further analysis (Figure 1). A database was established to display the study characteristics of each eligible study (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore excluded this study from Arg194Trp analysis. After removing these ineligible studies, a total 19 studies with 3387 cases and 6168 controls for Arg399Gln (G>A) polymorphism [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], 12 studies with 2043 cases and 4550 controls for Arg194Trp (C>T) [17], [18], [20], [21], [22], [23], [24], [25], [26], [28], [29], [32], and 6 studies with 1445 cases and 1905 controls for Arg280His (G>A) [15], [22], [23], [26], [28], [30] were included for further analysis (Figure 1). A database was established to display the study characteristics of each eligible study (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between these XRCC1 polymorphisms and leukemia risk has been examined in some case­-control studies, but the results of these studies were contradictory and inconclusive. Although the association between XRCC1 polymorphisms and risk of some types of leukemia was recognized by a number of studies [15], [17], [20], [21], [22], [23], [24], [25], [27], [28], [29], [32], [33], other reports did not take the XRCC1 genetic variants as risk or protective factors for leukemia [16], [18], [19], [26], [30], [31]. We conducted a meta-analysis that includes 19 studies for Arg399Gln (G>A) polymorphism, 12 studies for Arg194Trp (C>T), and 6 studies for Arg280His (G>A) to evaluate XRCC1 genotype-leukemia association (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has been revealed that XRCC1 Arg194Trp SNP (rs1799782) is a functional polymorphism and could affect the XRCC1 role, decrease the kinetics of repair mechanism, and influence susceptibility to cancer [25,26]. The role of XRCC1 polymorphisms in susceptibility to acute myeloid leukemia (AML) [27][28][29], acute lymphoblastic leukemia [30], chronic lymphocytic leukemia [31], and lymphoma [32] have been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the XRCC1 polymorphisms have been extensively studied in relation to acute myeloid leukemia (AML) [3, 13, 15, 16], acute lymphoblastic leukemia [1719], chronic lymphocytic leukemia [20, 21], and lymphoma [2226]. …”
Section: Introductionmentioning
confidence: 99%